2019
DOI: 10.3346/jkms.2019.34.e110
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin-Guided Treatment on Duration of Antibiotic Therapy and Cost in Septic Patients (PRODA): a Multi-Center Randomized Controlled Trial

Abstract: Background The objective of this study was to establish the efficacy and safety of procalcitonin (PCT)-guided antibiotic discontinuation in critically ill patients with sepsis in a country with a high prevalence of antimicrobial resistance and a national health insurance system. Methods In a multi-center randomized controlled trial, patients were randomly assigned to a PCT group (stopping antibiotics based on a predefined cut-off range of PCT) or a control group. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
(56 reference statements)
0
26
0
1
Order By: Relevance
“…[ 42 ]. Similarly, two recent trials from Greece and South Korea found a reduction in antibiotic use of up to 5 days but only the larger Greek study found a reduction in mortality [ 62 , 120 ]. Despite the heterogeneity of the data, overall results suggest that PCT is a good and safe complementary tool to discontinue antibiotics in sepsis, thus reducing antibiotic exposure, while its possible positive effect on mortality requires further research [ 47 , 121 ].…”
Section: Intensive Care Unit (Icu)mentioning
confidence: 99%
“…[ 42 ]. Similarly, two recent trials from Greece and South Korea found a reduction in antibiotic use of up to 5 days but only the larger Greek study found a reduction in mortality [ 62 , 120 ]. Despite the heterogeneity of the data, overall results suggest that PCT is a good and safe complementary tool to discontinue antibiotics in sepsis, thus reducing antibiotic exposure, while its possible positive effect on mortality requires further research [ 47 , 121 ].…”
Section: Intensive Care Unit (Icu)mentioning
confidence: 99%
“…The use and usefulness of PCT as a biomarker is covered extensively in literature in two main areas: as an early marker of sepsis (differentiating bacterial and non bacterial etiologies) and as a guide to the management of antibiotic therapy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In recent decades, there has been a shift in the focus on PCT as a biomarker able to guide the discontinuation of antibiotic therapy, particularly in critically ill patients (5,7,9,10,(12)(13)(14)(15)(16)18), demonstrating its safety and efficacy either alone or in association with other biomarkers, such as C-reactive protein (CRP), alpha 2 macroglobulin (A2M) and presepsin (19,21,22).…”
Section: Pct In Infected Critically Ill Patientmentioning
confidence: 99%
“…Conversely, in other trials the real efficacy provided by PCT in guiding the clinician's diagnosis has been questioned (7,8,10,11,19,23). Jeon et al (9) confirmed the role of PCT as a biomarker capable of reducing the duration of antibiotic treatment, but found that its use did not impact on clinical cure, 28-day mortality, in-hospital mortality, ICU length of stay and overall hospital length of stay, when comparing the PCT-guided and the control group of patients. Pepper et al evaluated the PCT-guided antibiotic discontinuation approach in a systematic review including 16 randomized clinical trials (RCTs) (23); they found that this approach was associated with decreased mortality (risk ratio, 0.89; 95% CI, 0.83-0.97) and with a decrease in antibiotics' duration (mean difference, 1.31 days; 95% CI, −2.27 to −0.35).…”
Section: Pct In Infected Critically Ill Patientmentioning
confidence: 99%
“…Herein, a prospective, randomized, controlled trial was performed by Jeon et al7 to assess the efficacy and safety of using PCT to guide antibiotic duration in the Korean ICU setting 7. From 4 sites in South Korea, 62 adult patients admitted to the ICU with presumed or proven infection were enrolled.…”
mentioning
confidence: 99%
“…Despite the strength of evidence described above,237 there are a few limitations to these studies that clinicians should be aware of before using PCT in practice 8. First, protocol adherence in the ICU based trials has been approximately 50% 237. How closely physicians outside of clinical trials adhere to evidence-based algorithms is unclear.…”
mentioning
confidence: 99%